2001
DOI: 10.1007/s001070050482
|View full text |Cite
|
Sign up to set email alerts
|

Damage evolution and acoustic emission of wood at tension perpendicular to fiber

Abstract: This paper presents the tracing of damage evolution in spruce loaded in tension perpendicular to ®ber direction by means of acoustic emission (AE) analysis. The 2 dimensional burst source location in cross-sectional slabs of boards utilized full wave form recording of AE signals monitored by six simultaneously triggered multiple resonant longitudinal (p±)wave sensors and fast transient recorder PC cards. The location algorithm was based on the minimization of the run time differences between experimental and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…A multitude of approaches focuses on this issue. The conventional AE analysis investigates the parameters of the AE signals in the time domain (Figure 1a) by means of AE signal amplitudes (Debaise et al 1966;Ansell 1982;Ando et al 1992a;Cunderlik et al 1996;Lee et al 1996;Aicher et al 2001;Kim et al 2005;Rosner 2012). Other studies focused on the AE frequency features (frequency domain, see Figure 1b) (Ogino et al 1986;Tyree and Sperry 1989;Reiterer et al 2000;Jakiela et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of approaches focuses on this issue. The conventional AE analysis investigates the parameters of the AE signals in the time domain (Figure 1a) by means of AE signal amplitudes (Debaise et al 1966;Ansell 1982;Ando et al 1992a;Cunderlik et al 1996;Lee et al 1996;Aicher et al 2001;Kim et al 2005;Rosner 2012). Other studies focused on the AE frequency features (frequency domain, see Figure 1b) (Ogino et al 1986;Tyree and Sperry 1989;Reiterer et al 2000;Jakiela et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies deal with the relationship between the stress level in wood under flexural loading and AE energy due to the fracture process [4] using ultrasonic sensors with a nominative frequency of 200 kHz. Aicher et al [5] have shown that using several ultrasonic sensors it was possible to locate the damage before the rupture. The influence of external parameters has been also reported, especially the variation in ambient relative humidity [6][7][8][9].…”
Section: Research Aimmentioning
confidence: 98%
“…This difference was attributed to differences in the fracture process zone formation in the two types of material. Aicher et al (2001) tracked damage localization phenomena by AE source locations, whereas Landis and Whittaker (2000) used an analysis of elastic waveform energy to measure the fraction of specimen fracture energy that is measured as AE energy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%